The negative effects of the COVID-19 epidemic crisis on the global tourism sectorand the support initiatives adopted in some countries to recover the sector. (Numerus academy review, 2026)
this study aims to determine the size of the negative impact that the Corona epidemic (COVID-19) has had on the global tourism sector, in addition to highlighting the mostimportant initiatives implemented in some countries of the world to support the recoveryof the tourism sector. The study concluded that global tourism, in light of the covid-19 pandemic, received severe unprecedented damage, which led to the loss of millions ofjobs and a significant decline in the revenues of the global tourism sector.